Cultural diversity in the adoption of open education in the Mediterranean basin: collectivist values and power distance in the universities of the Middle East - Cachia, Romina; Aldaoud, Mohammed; Eldeib, Ayman M.; Hiari, Omar; Tweissi, Adiy; Villar-Onrubia, Daniel; Wimpenny, Katherine; Maya Jariego, Isidro (Araucaria, 2020)
In this paper, we examine how open education is adopted in the Middle East region in the context of a European-funded project for capacity building in Higher Education. Basing our study on Hofstede’s model, we examine how culture, in particularly collectivism and power distance influence the adoption of open education. In addition, we look at the relationship between internationalisation of tertiary education and open education. Based on in-depth interviews, focus group, and participatory action research with experts in the fields from Egypt, Jordan, Lebanon and Palestine, our findings suggest that beyond the technical aspect and the development of content, adoption of open education in the Middle East region is influenced by cultural aspects, which needs to be taken into consideration. As an emerging sub-culture, open education has the potential to transform and change some cultural barriers related to both power distance and collectivist cultures.